Recycling of desulfurization slag for the production of autoclaved aerated concrete. (15th January 2018) - Chen, Ying-Liang; Ko, Ming-Sheng; Chang, Juu-En; Lin, Chun-Ta
Highlights: Desulfurization slag has the potential to produce autoclaved aerated concrete. The foaming of mortars is retarded due to the insufficient alkalinity. Using 0.17 M NaOH(aq) or calcining desulfurization slag can improve mortar foaming. Improving foaming results in the products with stable physical properties. The formation and morphology of tobermorite are affected by the slag added. Abstract: The purpose of this study was to reuse desulfurization (De-S) slag in the production of autoclaved aerated concrete (AAC). The non-magnetic fraction of De-S slag is rich in calcium and silicon compounds, and therefore suitable to be an alternative raw material for AAC production. The calcium compounds in the De-S slag used in this study were Ca(OH)2, CaCO3, γ-Ca2 SiO4, and CaF2 rather than CaO, and they affected the foaming of AAC mortars due to the insufficient alkalinity. Using 0.17 M NaOH(aq) to replace water or calcining the De-S slag in advance both improved the foaming of mortars, and thus obtained AAC products with stable properties. The formation and morphology of tobermorite in AAC were altered by the addition of De-S slag, probably due to the foreign ions introduced by the slag. The changes in tobermorite should also be related to the decline in the compressive strength of AAC specimens.